Meningkatkan Literasi Bahasa pada Anak Usia Dini Melalui Media Game Edukasi - Barokah Widuroyekti; Hadiqotul Luluk; Iswati (Institut Agama Islam Negeri Madura, 2023)
This study aims to determine the effectiveness of My Recreational Educational Games in increasing language literacy in early childhood in Jember Regency. The research subjects were 100 early childhood teachers. The research method used a quasi-experimental design, with the sampling technique using random sampling technique. The results showed that there was a significant change in the pretest results in the experimental class. My Recreational Educational Game has a colorful display, the content of the application does not contain pornographic elements, is in accordance with science and technology development, the arrangement of appropriate sentences and attractive pictures and simple language so that children are interested in learning. By utilizing the educational game Rekreasiku, there is a suitable alternative because this Android-based educational game has the advantage of having an attractive appearance and simple language. My Recreation educational game encourages young children to carry out educational activities in a fun way. My Recreational Educational Game has a significant effect on the development of children's literacy in early childhood.